Pengaruh Model PBL Berbantuan Flip Book terhadap Kemampuan Berfikir Kritis Siswa Sekolah Dasar - Niken Anjarsari; Rissa Prima Kurniawati; Cerianing Putri Pratiwi (Universitas PGRI Madiun, 2022)
The purpose of this study was to describe the effect of the PBL model with the help of a flip book on the critical thinking skills of elementary school students. This type of research is quantitative with quasi-experimental (quasi-experimental). The design in this study was a posttest only control design. The population taken in this study was SDN 02 Milangasri 1 and SDN Milangasri 3. The sample of this study was taking class V which was used as the control class and the experimental class. The sampling technique in this study was random sampling. Data collection techniques using a test (posttest), and documentation. The instruments used are validity and reliability tests. Validity test using product moments correlation and test using alpha test reliability. Data analysis using prerequisite test (normality test and homogeneity test) and hypothesis testing with twin sample t-test. The results showed that there was a significant difference in students' critical thinking skills with the PBL model with ttable = 2,086> tcount = 0.63364. Based on the results of the posttest carried out, there is an effect of the PBL model with the help of a flip book on the critical thinking ability of elementary school students